MULTIMOD : A Multi-Region Econometric Model. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The paper describes a global model consisting of several industrial and developing country blocks built to analyze alternative economic policies in a medium-term context. The model, which has been used to construct medium-term scenarios for the World Economic Outlook, consists of aggregate demand and supply relationships, with endogenous determination of interest rates, prices, and exchange rates. Financing flows to developing countries depend on expectations of their ability to service debt. Expectations of interest rates, inflation, and exchange rates are modeled in a way that is consistent with the model's solution, and budget constraints are imposed on governments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet